Clinical Efficacy of CyberKnife Radiosurgery for Adult Brainstem Glioma: 10 Years Experience at Tianjin CyberKnife Center and Review of the Literature - Zhang, Jiaqi; Liu, Qun; Yuan, Zhiyong; Zhao, Lujun; Wang, Xiaoguang; Wang, Ping (Frontiers in Oncology, 2019)
Abstract Background Brainstem glioma is a rare brain tumor with poor prognosis and difficulty for surgical resection. We sought to retrospectively analyze and evaluate the clinical efficacy of CyberKnife for brainstem gliomas. Methods From 2006 to 2015, a total of 21 brainstem gliomas patients who received CyberKnife radiosurgery treatment enrolled in this study and 18 patients with follow up. CyberKnife image-guided radiosurgical system were applied consecutively with the median prescribed total dose of 26 Gy (14-33 Gy) at two to six fractions on days utilizing CyberKnife system, and the median biological equivalent doses of 59.8 Gy (33.6-76.56Gy). The clinic pathlogical features, survival were analyzed to explore the efficacy of CyberKnife radiosurgery in treatment of brainstem glioma. Results With median follow-up of 54.5 months, patients with brainstem gliomas had median overall survival of 19 months, 5 patients still alive. The primary endpoints of the 1- and 2-year overall survival rates were 87.5% and 52.4%, respectively. During the treatment course, six patients were observed to have pseudoprogression with mass effect on MRI. Four patients developed radiation complications. Grade 2 radiation-related toxicity were observed in three patients and one patient with grade 3. Conclusion The efficacy of brainstem gliomas – treated with CyberKnife is efficacious with mild toxicity.